Preserving Identity in a Globalized World: Strategies for Maintaining the Bugis-Makassar Language Based on Seminar Participants’ Perspectives - Kembong Daeng; Ilma Rahim; Fatimah Yunus; Ita Rosvita; Bungatang Bungatang (Pustaka Digital Indonesia, 2026)
The rapid advancement of globalization has significanty impacted the sustainability of regional languages, including the Bugis-Makassar language, leading to a decline in its use among younger generations. This study aimed to examine strategies for maintaining the Bugis-Makassar language as a mother tongue in the context of globalization, focusing on participants’ perceptions of the International Mother Tongue Seminar. The study employed a descriptive quantitative approach supported by qualitative analysis to provide a comprehensive understanding of language awareness, attitudes, and preservation strategies. The study involved 120 respondents from diverse backgrounds, including students, academics, teachers, and the general public, selected through purposive sampling. The data were collected using a structured questionnaire based on a 5-point Likert scale, complemented by open-ended questions to capture deeper insights. The research instrument was tested for validity using Pearson Product Moment correlation and for reliability using Cronbach’s Alpha, yielding a coefficient of 0.87, indicating high internal consistency. Quantitative data were analyzed using descriptive statistics, including mean, percentage, and standard deviation, while qualitative data were examined through thematic analysis. The findings revealed a high level of awareness among respondents regarding the importance of the Bugis-Makassar language as a cultural identity. However, a gap existed between awareness and actual language use, particularly in formal and digital contexts. The seminar was positively evaluated as an effective platform for raising awareness. Key strategies identified include integrating regional languages into formal education, strengthening intergenerational transmission, and utilizing digital media for language revitalization. In conclusion, although awereness of the importance of Bugis-Makassar language is relatively high, practical usage remains limited, indicating the need for more structured and sustainable preservation stategies supported by educational institutions and digital innovation.